Analisis Faktor yang Mempengaruhi Produktivitas Tenaga Kerja Pemanen Kelapa Sawit - Mita Puspita Sari Sitio; Faoeza Hafiz Saragih; Cut Gustiana (Universitas Medan Area, 2026)
This study aims to determine the effect of wages, work experience, age, and harvest premiums on the productivity of oil palm harvesters at PTPN IV Regional VI North Julok Rayeuk Plantation, East Aceh. This study was conducted at the North Julok Rayeuk Plantation, East Aceh. The sampling technique used was the random sampling technique with a sample of 35 harvest employees at PTPN IV Regional VI North Julok Rayeuk Plantation, East Aceh. The data used in this study comprises both primary and secondary data. The data analysis method used in this study is multiple linear regression analysis. The results of the study indicate that simultaneously, there is an influence of wages, work experience, age, and harvest premiums on the productivity of oil palm harvesters. Partially, the work experience variable does not affect the productivity of oil palm harvesters, while the variables of wages, age, and harvest premiums have a significant effect on the productivity of oil palm harvesters at PTPN IV Regional VI North Julok Rayeuk Plantation, East Aceh.